A organização social primitiva dos caçadores e coletores - Silva, Yuri (2023)
During the initial stages of human social organization, in groups of hunters and gatherers, the development of productive forces was limited, resulting in an absence of exploitation of man by man. The low productivity of labor and the lack of surplus production prevented the existence of classes. With the introduction of agriculture, the division of labor gradually deepened, which implied a subsequent separation between "intellectual work" and "manual work". Communities of horticulturists and hunter-gatherers were characterized by social equality, collective ownership of the means of production and gender equality, representing a communist character of the relations of production. However, the Neolithic Revolution brought changes such as private ownership of the means of production, social inequality and gender subordination. Despite the primitive level of productive forces suggesting homogeneity and monotonous relations, the substantial equality in these communities allowed significant individual development within material limitations. Understanding this individual development in primitive societies is crucial to guide contemporary social practices, especially in education. Therefore, the equality in the relations of production in these early communities, despite the material limitations, allowed a remarkable individual development and offers valuable lessons for current social actions.